Influence of porosity on ultrasonic wave velocity, attenuation and interlaminar interface echoes in composite laminates: Finite element simulations and measurements. (15th September 2016) - Ishii, Yosuke; Biwa, Shiro; Kuraishi, Akira
Abstract: The influence of porosity on the ultrasonic wave propagation in unidirectional carbon-fiber-reinforced composite laminates is investigated based on the two-dimensional finite element analysis and measurements. Random distributions of pores with different contents and size are considered in the analysis, together with the effects of viscoelastic plies and interlaminar resin-rich regions. The transient reflection waveforms are calculated from the frequency-domain finite-element solutions by the inverse Fourier transform. As the measures for porosity characterization, the ultrasonic wave velocity, attenuation coefficient, and interlaminar interface echo characteristics are examined for 24-ply unidirectional composite laminates. As a result, the wave velocity decreases with the porosity content in a manner insensitive to the pore size. On the other hand, the attenuation coefficient increases both with the porosity content and with the pore size. The time–frequency analysis of the reflection waveforms shows that the temporal decay rate of interlaminar interface echoes at the stop-band frequency is a good indicator of the porosity content. The measured porosity-content dependence of the wave velocity is better reproduced by the numerical simulations when the interlayer interfacial stiffnesses are adjusted according to the porosity content, indicating that not only the porosity features but also the interlaminar interfacial properties vary with curing conditions.